GAMBARAN INTERAKSI OBAT HIPOGLIKEMIK ORAL (OHO) DENGAN OBAT LAIN PADA PASIEN DIABETES MELITUS (DM) TIPE II DI APOTEK IMPHI PERIODE OKTOBER 2014 SAMPAI MARET 2015 - Aries Meryta; Mega Efrilia; Pra Panca Bayu Chandra (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2015)
Increasing complications of diabetes mellitus (DM) have tendency to amount of drug use, which can increase the risk of drug interaction. Drug interaction is a situation arising of administrations more than one drug at the same time that effects each drug can be interfere each other and or both are mutually and or undesirable side effect may a rise which could potentially harm and or doesn’t give clinically significant effect. This research aims to determinate the potential interactions and mechanisms of drug interactions and impacts based on the severity of the effect of therapy in patients type II of diabetes mellitus (DM) at Imphi’s Pharmacy in the period October 2014 until March 2015. The research used descriptive evaluative and retrospective method based on recipe sheets. Data analysis have done by screening of drug interaction and using drug interaction from software lexicomp and drug interaction stockley. The results showed that there are 28 recipe sheets (16,37%) from 171 recipe sheets of 110 patients that potentially occur pharmacodynamic mechanism of drug interaction with as many as 36 events (64,29%) as well as the mechanisms of drug interaction based on the severity of the effect of moderate kind of therapy as much as 40 events